Hybrid-Based Arabic Language Learning Model In University - Sunarko, Asep; rahayu, siska; Nurul Anjani Safitri, Siti (AJIRSS: Asian Journal of Innovative Research in Social Science, 2025)
This study aims to analyze the Arabic language learning method based on hybrid learning at the University of Quranic Sciences (UNSIQ). Using a descriptive qualitative approach and case study design, the research explores the implementation, characteristics, and challenges of hybrid learning models in Arabic language education. Data collection methods include participatory observation, in-depth interviews, and documentation. Research findings demonstrate that the hybrid model at UNSIQ integrates face-to-face and online learning, resulting in an innovative pedagogical approach that enhances students' Arabic language competence. The findings reveal the advantages of the hybrid model, such as learning flexibility, digital skill development, and increased learning motivation. However, the study also identifies significant challenges, including technological infrastructure limitations, variations in digital competence among lecturers and students, and curriculum design complexities. The research concludes that hybrid learning models have the potential to transform Arabic language education, with the note that institutional support, continuous development, and multi-stakeholder commitment are necessary for successful implementation.